Strategic Collaborative Planning for Urban Liveability: A Comparative Review of Metropolitan Area Case Studies - Zanudin, Khalid; Wikantiyoso, Respati; Bidin, Zafikha Aida; Rashid, Mohamad Fadhli (International Journal of Sustainable Construction Engineering and Technology, 2023)
The issue of urban liveability has been extensively debated by global agencies and scholars, as evidenced by the New Urban Agenda, in response to the impact of urbanisation. Urban liveability pertains to the ability of urban communities to achieve a high-quality living environment. While participatory planning is often presented as a means of empowering communities to attain better living conditions, it has presented challenges for decision-makers. Furthermore, dominant actors often influence participation processes, benefiting certain community segments. As a result, collaborative planning has emerged as an approach that seeks to address the interests of multiple urban factors by promoting consensus in decision-making. This paper aims to examine the collaborative planning methods that have been used in strategic planning that have empowered the community to participate in the planning process. Content analysis was employed as a research method to explore the empirical evidence of collaborative planning that has successfully empowered community participation in strategic planning and its impact on the liveability of metropolitan areas. Correspondingly, the Melbourne, Vancouver, and Helsinki case studies were selected based on five liveable city indices. This study's findings suggest a positive correlation between the implementation of collaborative planning by the selected metropolitan areas and their status as the most liveable cities. This paper contributes to the ongoing debate on the role of collaborative planning in promoting urban liveability.